DRIS nutritional norms and sufficiency range for the perola pineapple cultivation - de Amorim, Daniel Angelucci; Favero, Ana Carolina; Conceição, Mariana Passos da; Vilela Rodrigues, Maria Geralda; Belarmino Rodrigues, João Batista; Natale, William; Rozane, Danilo Eduardo [UNESP] (Taylor & Francis, 2024)
Pineapple plants needs to be nutritionally balanced to reach maximum productivity potential. Therefore, the most current parameters must be used, centered on plant nutritional status diagnosis methodologies developed through leaf chemical analysis, which consider the relationships between nutrients and take advantage of data from productivity monitoring and foliar diagnosis of crops. This study aimed to establish nutrient norms and sufficiency ranges for pineapple in the Triângulo Mineiro, MG, Brazil, using the Diagnosis and Recommendation Integrated System (DRIS). To achieve the proposed objectives, productivity data and chemical analysis of leaf tissue from 88 commercial farming plots of 'Pérola’ pineapple, sampled between the 2018 and 2019 harvests, in the Triângulo Mineiro were used. The DRIS method was used to establish the norms and sufficiency ranges of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn. The average nutritional balance index (NBIm) did not correlate with productivity. However, the content of P, Ca, Mg, S, B, Cu, Fe, Mn, and Zn highly correlated with their respective nutritional indices. The sufficiency ranges and the adequacy levels of nutrients differed from the values established for pineapple in the literature.
Keywords: Ananas comosus; foliar diagnosis; nutritional status assessment